EXPLORING HALAL CERTIFICATION AND IMPACT ON BUSINESS FOR MSME’s - Yanti, Vanda Sekar (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2024)
This study investigates the impact of halal certification on brand trust, consumer perception quality, and business performance for Small and Medium Enterprises (SMEs). Using quantitative methods, data was collected through surveys from SMEs operating in a specific region. The results indicate a significant positive relationship between halal certification and both brand trust and consumer perception quality. Additionally, brand trust and consumer perception quality were found to positively influence business impact for SMEs. However, the study acknowledges limitations related to sampling biases and regional specificity. Future research is recommended to broaden the scope and consider qualitative methods for deeper insights. Overall, this study underscores the importance of halal certification in enhancing brand trust, consumer perception quality, and business performance for SMEs.